Detection of wormhole attack in mobile ad-hoc networks - Sanaei, Mojtaba Ghanaatpisheh (2013)
An ad-hoc network is a group of wireless mobile node that shapes a temporary network without any infrastructure and centralized management. Each mobile node functions are not only restricted to base station but also as router for forwarding packets to other mobile nodes in the network. One primary application of Mobile Ad-hoc Networks (MANETs) is for military purpose including the tactical operations where security is often the major concern. The different leaks that threaten the security of wireless network contain, selective forwarding, wormhole attack, Sybil attack, sinkhole attack and black hole attack. One of the dangerous attacks in mobile ad hoc network is named as wormhole attack in which two or more destructive nodes record the packets at one point and transmits them by a wired or wireless to another point in the network. Wormhole attack is so strong and detection of this attack is hard. Also, the wormhole attack may cause another type of attacks like Sinkhole or Select forwarding. The using a cryptographic technique is not enough to prevent wormhole attack. So, in this study, a new method is proposed based on modifying the forwarding packet process and also using a delay per hop and expiry time technique to detect wormhole. The performance evaluation of the proposed method is done using a mathematical modeling and simulation.